2016
DOI: 10.1097/brs.0000000000001554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraoperative Anesthetic Medications on Postoperative Urinary Retention After Single-Level Lumbar Fusion

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The range reported in the spine literature is 5.6% to 30%. [3][4][5]7,9 In our study, POUR rates were on the higher spectrum of this range; however, it included patients who had revision surgery (48.9%) and excluded those operated at another spine region (cervical spine). In his retrospective analysis of POUR in patients undergoing elective spine surgery, Altschul et al 2 reported an incidence of POUR of 8.8%.…”
Section: Incidence Of Pourmentioning
confidence: 99%
“…The range reported in the spine literature is 5.6% to 30%. [3][4][5]7,9 In our study, POUR rates were on the higher spectrum of this range; however, it included patients who had revision surgery (48.9%) and excluded those operated at another spine region (cervical spine). In his retrospective analysis of POUR in patients undergoing elective spine surgery, Altschul et al 2 reported an incidence of POUR of 8.8%.…”
Section: Incidence Of Pourmentioning
confidence: 99%
“…Previous research has demonstrated that intraoperative usage of phenylephrine and neostigmine may increase the risk of developing POUR. 45 Although isolated cases of POUR may resolve without serious clinical consequences, surgeons should be mindful of this complication arising in lumbar fusion procedures as a sequelae of compressive epidural hematoma resulting in cauda equina syndrome. The rate of POUR has been determined to be as high as 20% following singlelevel MIS lumbar fusion procedures.…”
Section: Postoperative Nausea and Vomitingmentioning
confidence: 99%
“…The rate of POUR has been determined to be as high as 20% following singlelevel MIS lumbar fusion procedures. 45 As increasing lumbar fusion surgeries are being performed in the ambulatory setting, essential considerations to keep in mind include the identification of risk factors that can prognosticate the development of postoperative POUR and avoiding the use of medications that may increase this risk.…”
Section: Postoperative Nausea and Vomitingmentioning
confidence: 99%
“…Several commonly used perioperative medications affect voiding function. Anticholinergics, volatile anesthetics, opioids, and scopolamine may contribute to detrusor underactivity via their antagonistic action on muscarinic receptors 20,24–26 . Although the authors of these studies speculate that nonsteroidal anti-inflammatory drugs may be associated with detrusor underactivity due to inhibition of prostaglandin-mediated detrusor muscle contraction, these theories are based on observational studies from other surgical subspecialties 56,121 …”
Section: Discussionmentioning
confidence: 99%
“…Studies specific to urogynecology have demonstrated that patient factors, such as medical history, prolapse stage, preexisting urinary symptoms, and preoperative urodynamic findings, are associated with POUR 16–26 . Perioperative factors, such as surgical route, concomitant procedures, surgical length, blood loss, anesthesia type, perioperative medications, intraoperative fluid management, and postoperative pain control, also may contribute to POUR 20,24–26 …”
Section: Introductionmentioning
confidence: 99%